Assessing Cultural Intelligence and Its Antecedents in the Portuguese Higher Education Context - Marina Sousa; Eunice Fontão; Isabel Machado; Jorge Mendonça; José Rodrigues; Carlos Freitas (MDPI AG, 2023)
The concept of cultural intelligence has been the object of increasing attention from the scientific community due to its importance in a globalized world. To fulfil their mission, higher education institutions need individuals capable of effectively interacting with others who come from different cultural backgrounds. This study analyzes the level of cultural intelligence and its background in a Portuguese engineering higher education institution. This study used a cultural intelligence scale and applied it to a sample of 445 participants. The results show that individuals in this Portuguese institution have an interesting level of awareness of others' cultural preferences. However, particular attention should be paid to improving the outcome of the cognitive dimension. The results show the potential of international experiences and activities that foster cultural exposure. Consequently, the managers of institutions should make efforts to promote Erasmus programs or similar internships abroad. In addition, they should promote activities that foster multicultural contact, whether extracurricular activities or multicultural clubs or associations, meetings, lectures or classes with appropriate pedagogical methodologies, for example, experiential or collaborative teaching.